2009
DOI: 10.1002/ange.200901495
|View full text |Cite
|
Sign up to set email alerts
|

Tellurium(II)‐Centered Dications from the Pseudohalide “Te(OTf)2

Abstract: Pyridin‐ oder Carbenderivate als Liganden ermöglichen die Synthese von tellurzentrierten Dikationen, darunter einem dikationischen Telluranalogon des kürzlich synthetisierten „Carbodicarbens“, in hoher Ausbeute. Entscheidend für den Zugang zu diesen Verbindungen ist die Isolierung einer basenstabilisierten Form von TeOTf2 (siehe Struktur), einem neuen hoch elektrophilen Reagens für die Tellurchemie.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
1
4
0
1
Order By: Relevance
“…The experimentally determined metrical parameters agreed well with the calculated values, confirming that the diimine bonding motif was retained, and ligand exchange reactions were demonstrated, which indicated that 2 b is a reasonable bonding model 2023. We have also synthesized a related tellurium derivative; however, covalent bonds were observed between the tellurium center and the triflate counterions, giving a neutral compound 24…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…The experimentally determined metrical parameters agreed well with the calculated values, confirming that the diimine bonding motif was retained, and ligand exchange reactions were demonstrated, which indicated that 2 b is a reasonable bonding model 2023. We have also synthesized a related tellurium derivative; however, covalent bonds were observed between the tellurium center and the triflate counterions, giving a neutral compound 24…”
Section: Introductionsupporting
confidence: 72%
“…Two of the other reports involve hemilabile complexes of Te II thiolates with bridging 4,4′‐bipyridine ligands containing very long TeN contacts of ∼2.8 Å 45. 46 The other example is a dicationic homoleptic Te II complex with four 4‐dimethylaminopyridine ligands in a square‐planar arrangement, featuring TeN bonds of ∼2.3 Å 24…”
Section: Resultsmentioning
confidence: 99%
“…This compound appears to have the potential to be used as a Te II source although no further chemistry utilizing the compound as a TeI 2 synthon has been reported. Very recently our group has reported the use of a Dipp‐BIAN‐stabilized pseudohalide of Te (Te(OTf) 2 ) to generate a series of Te‐centered dications 29. However, a viable source of TeCl 2 remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Attempts to use a different Cu + source CuOTf[MeCN] 4 yielded similar results as reactions performed with CuCl. As an alternative to the coinage metal induced ring expansion of 1Ch, the parent 6-membered rings 2Ch could be reacted directly with the metal species (CuCl, AgOTf) in 1:1 stoichiometry to yield 7 Ch M that were isolated in yields comparable to those 33,34 The 31 P{ 1 H} NMR spectrum of 7 S Ag displayed a broad singlet, likely indicating a dynamic process in solution (Figure 6). In contrast, the selenium congener 7 Se Ag showed two sharp doublets with selenium satellites ( 107 Ag: 1 J Ag−P = 185.8 Hz; 109 Ag: 1 J Ag−P = 213.2 Hz; 1 J Se−P = 151.8 Hz; Figure 7).…”
Section: ■ Results and Discussionmentioning
confidence: 99%